Application of the Al-Miftah Lil Ulum Method to Improve the Speed of Reading the Unvowelled Arabic Texts - Mohammad Hasan Khoirul Anwar; Izzul Haqqi; Endah Tri Wisuda Ningsih (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to examine the implementation of the Al-Miftah Lil Ulum method in improving the reading speed of unvowelled Arabic texts (kitab gundul) among ibtidaiyah-level students at Pondok Pesantren Raudlatul Hasan Maron Probolinggo. A descriptive qualitative approach with a case study design was employed. Data were collected through classroom observations, in-depth interviews with pesantren leaders, the head of the kitab learning institution, and instructors, as well as documentation of learning activities. The findings indicate that the Al-Miftah Lil Ulum method is systematically implemented through four progressive instructional volumes focusing on basic word identification, contextual understanding, mastery of verb patterns, and i‘rab analysis. The method significantly improves students’ reading speed and accuracy, while also enhancing motivation, confidence, and learning autonomy through the integration of nadzam, direct practice, and authentic assessment. These findings highlight the crucial practical implications of the Al-Miftah Lil Ulum method for pesantren education, particularly as a structured instructional model that accelerates kitab literacy acquisition without compromising grammatical accuracy. The implementation of this method offers an effective strategy for pesantren to improve the quality of graduates more efficiently, strengthen the culture of classical text literacy, and respond to the demands of educational modernization while preserving the integrity of traditional Islamic scholarship